Inequalities in HPV vaccine offer among Italian regions: Analysis of regional prevention plans - Melissa Torrisi; Virginia Casigliani; Eugenio Mammolenti; Andrea Porretta; Caterina Rizzo; Lara Tavoschi (Human Vaccines & Immunotherapeutics)
Human papillomavirus (HPV) infection is a major cause of cervical cancer and other anogenital and oropharyngeal neoplasms. Vaccination against HPV has proven to be an effective tool in preventing these diseases. However, there are significant disparities in vaccine offer among different Italian regions. This study analyzes the vaccination strategies and offer of Italian regions for HPV vaccination, focusing on the implementation of the Italian National Vaccination Prevention Plan (PNPV) 2023–2025. Data were collected through web research. The variables examined included the availability of free vaccination for age and gender groups, catch-up strategies for unvaccinated women, and free vaccine offer for population groups with specific risk conditions. As of May 30, 2025, all regions received the PNPV 2023–2025 and formulated their vaccination regional plan accordingly. The regions showed significant variability in this process, both in the timing of the approval of the regional plan and in the offer. Differences in vaccine offer were observed by age and specific risk conditions, such as for sex workers and other sexual behaviors at risk and people with specific health conditions (e.g. non-HIV related immunosuppression). This study highlighted the need for a coordinated and uniform approach to HPV vaccination in Italy. Timely and uniform adoption of the PNPV 2023–2025 through the formulation of vaccination regional plans is crucial to reducing health inequalities and improving HPV-related health outcomes.